Adolescent Premarital Sexual Behavior: A Narrative Review of Challenges, and the Vital Role of Comprehensive Sex Education in Promoting Health and Well-being in Islamic Countries - Lamia Abdulgalil Saif Ali Al-amri; Brihastami Sawitri; Haitham T. S. Mohammed; Hebah Hamood Moqbel (Jurnal Psikiatri Surabaya, 2024)
Introduction: Adolescents, comprising 1.2 billion globally, face unique challenges during the transformative phase of sexual maturation. This review emphasizes the prevalence of premarital sexual behavior among adolescents, with a focus on Southeast Asia, Indonesia, and Arab nations. The vulnerable nature of this age group is underscored, considering the risks of unsafe abortions, unintended pregnancies, and sexually transmitted diseases. Objective: The primary objective is to offer a comprehensive understanding of premarital sexual behavior in adolescents. By synthesizing recent developments and key findings, this review aims to inform specialists and non-specialists, foster societal dialogue, and serve as a resource for scholars and practitioners interested in adolescent sexual health. Methods: Utilizing PubMed and Google Scholar, an extensive literature search spanning 2018 to 2023 focused on keywords such as "adolescent AND sex” The inclusion criteria involved articles directly aligned with the review's scope, leading to the identification of 20 relevant articles. Results: Factors influencing adolescent sexual behavior, and the impact of cultural, religious, and societal norms were explored. The importance of sex education, particularly comprehensive sexuality education, in addressing premarital sexual behavior emerged as a critical theme. The impact on adolescent health, both physical and mental, was also highlighted. Conclusions: Premarital sexual behavior among adolescents is a complex issue influenced by various internal and external factors. Comprehensive sexuality education, incorporating cultural and religious teachings, is crucial in promoting healthy decision-making and preventing negative consequences. The review emphasizes the need for ongoing discussions, further research, and improved sexual health education globally.